PENGARUH PEMBERIAN TEPUNG KEDELAI KAYA ISOFLAVON TERHADAP KADAR MALONALDEHID (MDA), AKTIVITAS SUPEROKSIDA DISMUTASE (SOD) TESTIS DAN PROFIL Cu,Zn-SOD TUBULI SEMINIFERI TESTIS TIKUS JANTAN [The effects of isoflavone-riched soybean flour on MDA Level, Sup - Sussi Astuti; Deddy Muchtadi; Made Astawan; Bambang Purwantara; Tutik Wresdiyati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2009)
The objectives of this experiment were to evaluate the effects of isoflavone-riched soybean flour with different treatment level of isoflavone on MDA level, SOD activity, and profile of Cu,Zn-superoxide dismutase (Cu,Zn-SOD) spermatogenic cells in the seminiferous tubules of male rat testes. Diet was given as isonitrogen and isocaloric with 10% of dietary protein. Twenty five males of Sprague Dawley rats were divided into five groups and treated with isoflavone-riched soybean flour by oral administration with different concentrations. The treatment was done for 2 months. The optimum concentration of isoflavone was 1.5 mg/day and resulted in : decreased level of MDA testes (2.29±0.05 nmol/g), mantained high SOD activity of rat testes (729.4±23.73 U/g), and increased content of Cu,Zn-SOD by immunohistochemical technique on spermatocytes and early spermatids. It was concluded that isoflavone-riched soybean flour diet (1.5 mg/day isoflavone) can prevent the formation of lipid peroxide and improve the antioxidant status of rat testes.